The Potential for Analyzing the Correlation Between the Compressive Stress Resistance of Red Clover Seeds and the Environmental Conditions during Seed Maturation Using FT-IR Spectroscopy - Gergely Zoltán Macher; Marcell Lócsi; Anett Bedo; Eszter Kókai; Dalma Bódizs; Szilveszter Gergely (Chemical Engineering Transactions)
The paper aims to examine the connection between environmental conditions during seed maturation and the ability of seeds to compressive stress, supported by statistically significant findings. The study involves using Fourier transform infrared (FT-IR) spectroscopic analysis on red clover seeds under varying pressure levels, specific tensions, and selected quality parameters. The methodology relies on a general FT-IR spectroscopic approach, with spectral comparisons made against results from pressure-induced rupture. Through this research, new methods for seed testing are intended to be informed by differential and correlation results across technical parameters and different measurement settings. The analyses indicated a noticeable difference of several 10 N in visible features between seed maturation stages and compressive tolerance. Given the novelty of the aspects being explored, one primary influencing factor is identified as the scarcity of available literature, which also serves as a limitation of this research. The obtained results have potential applications for analysts, agricultural specialists, consultants, and experts involved in seed management and distribution.